OBSERVATION ON THE FLIGHT PERIOD OF DALACA CHILIENSIS (VIETTE, 1950) AT THE VALDIVIA PROVINCE CHILE (LEPIDOPTERA: HEPIALIDAE) (Acta Entomológica Chilena, 2022)
To record the flying period of Dalaca chiliensis (Viette, 1950) through daily capture with phototropic trap and it is indicated some climatic and behavior conditions of this species in such flying period.The short life cycle from the adults of D. chiliensis, points out an effective isolation strategy, because it does not overpass the flight of other species of the genus. A short adult life, would be showing a prolonged larval life phase, which would difficult the control of this species. It is concluded that the abundance of this species in its flight period is not influenced by the climatic variables; it has a crepuscular and nocturnal flight
Keywords: Dalaca chiliensis, activity of flying, Hepialidae, behaviour, Chile